Contested Knowledge and Information Behaviour: Treatments for Depression - Oliphant, Tami (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
A wide variety of treatment options for depressives have been developed by both the conventional and complementary and alternative medicine (CAM) sectors. Using data collected from three online newsgroups as well as in-depth interviews, I analyze how people use information when making or justifying claims, or making decisions, about treatments for depression. Les personnes souffrant de dépression ont une grande variété d'options de traitement à leur disposition, y compris les méthodes conventionnelles et les méthodes complémentaires ou alternatives. À l'aide de données recueillies à partir de trois forums en ligne et d'entrevues en profondeur, j'ai analysé comment les gens utilisent cette information pour déclarer, justifier leurs déclarations ou encore choisir les traitements contre la dépression. ***Student to CAIS/ACSI Award Winner***